Ex 2.2, 1 - 3 sin-1 x = sin-1 (3x - 4x3) - Chapter 2 Inverse

Ex 2.2,1 - Chapter 2 Class 12 Inverse Trigonometric Functions - Part 2

  1. Chapter 2 Class 12 Inverse Trigonometric Functions
  2. Serial order wise

Transcript

Ex 2.2, 1 3sin-1 π‘₯ = sin-1 (3π‘₯ βˆ’ 4π‘₯^3), π‘₯∈ [βˆ’1/2,1/2] Solving R.H.S sin^(βˆ’1) (3π‘₯ βˆ’ 4π‘₯^3) Putting x = sin πœƒ = sin^(βˆ’1) (3 sin πœƒ βˆ’ 4 γ€–"sin" γ€—^3πœƒ) = sin^(βˆ’1) (sin 3πœƒ ) = 3πœƒ = 3 〖𝑠𝑖𝑛〗^(βˆ’1) x (sin 3x = 3 sin x βˆ’ 4 sin^3x) Now, x = sin πœƒ sinβˆ’1 x = πœƒ = L.H.S Hence, proved.

About the Author

Davneet Singh's photo - Teacher, Engineer, Marketer
Davneet Singh
Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 10 years. He provides courses for Maths and Science at Teachoo.